Report from the 11th Conference of the “Biograf” Journal : 19th–21st June, 2009, Hoješín u Seče, Czech Republic, http://www.biograf.org/konference/ - Vaňková, Markéta (Lidé města, 2009)
The 11th conference of the “Biograf” journal brought several surprises. The first one was the conference itself because in the past year the working session of the authors and friends of the Biograf did not take place and the continuation of the long and popular tradition could have been endangered. Fortunately (in my opinion at least) these fears were baseless and the 11th working session of the Biograf journal took place in the last third of June.